Localization of METTL16 at the Nuclear Periphery and the Nucleolus Is Cell Cycle-Specific and METTL16 Interacts with Several Nucleolar Proteins - Stixová, Lenka; Komůrková, Denisa; Svobodová Kovaříková, Alena; Fagherazzi, Paolo; Bártová, Eva (Life (Basel, Switzerland), 2021)
METTL16 methyltransferase is responsible for the methylation of N6-adenosine (m6A) in several RNAs. In mouse cells, we showed that the nuclear distribution of METTL16 is cell cycle-specific. In the G1/S phases, METTL16 accumulates to the nucleolus, while in the G2 phase, the level of METTL16 increases in the nucleoplasm. In metaphase and anaphase, there is a very low pool of the METTL16 protein, but in telophase, residual METTL16 appears to be associated with the newly formed nuclear lamina. In A-type lamin-depleted cells, we observed a reduction of METTL16 when compared with the wild-type counterpart. However, METTL16 does not interact with A-type and B-type lamins, but interacts with Lamin B Receptor (LBR) and Lap2α. Additionally, Lap2α depletion caused METTL16 downregulation in the nuclear pool. Furthermore, METTL16 interacted with DDB2, a key protein of the nucleotide excision repair (NER), and also with nucleolar proteins, including TCOF, NOLC1, and UBF1/2, but not fibrillarin. From this view, the METTL16 protein may also regulate the transcription of ribosomal genes because we observed that the high level of m6A in 18S rRNA appeared in cells with upregulated METTL16.
Keywords: rDNA; METTL16; epitranscriptome; nucleolus; cell cycle